PEMILIHAN METODE AKUNTANSI PERSEDIAAN DAN PENGARUHNYA TERHADAP EARNING PRICE RATIO - Soesetio, Yuli (IQTISHODUNA, 2008)
This research was conducted to know investment production opportunity in the inventory variable, accounting profit variable, HPP variable, company’s siz, equity intensity and inventory intensity, and to know the effect of option the accounting inventory methods (FIFO) and average methods towards earning price ratio. Data taken from secondary data with using documentation methods and purposive sampling methods with 10 companies. Using sample manufacturing’s comp[any which listed in Jakarta Stock Exchange period 2001-2005. using data analysis Mann-Whitney and t-test, log regression and parametric test. The result of univariat test indicated that just inventory intensity variability which using average inventory methods FIFO methods which has significant differences.